2019
DOI: 10.3390/polym11071142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Room Temperature Vulcanized Silicone Rubber Using Methoxyl-Capped MQ Silicone Resin as Self-Reinforced Cross-Linker

Abstract: Methoxyl-capped MQ silicone resin (MMQ) was first synthesized by the hydrosilylation of vinyl-containing MQ silicone resin and trimethoxysilane and then used in condensed room-temperature vulcanized (RTV) silicone rubber as a self-reinforced cross-linker. Results show that modified silicone rubber exhibits good light transmission. Compared with unmodified silicone rubber, the hardness, tensile strength and elongation of MMQ at the break are increased by 26.4 A, 2.68 MPa and 65.1%, respectively. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The concentration of the unreacted cross-linker decreased over time, reaching 0 wt% after 17 days as additional cross-linker domains were created. Since silsesquioxanes are generally known to be self-reinforcing cross-linkers [16][17][18][19][20][21], (QM OEt ) 8 cross-linker domains are expected to have a positive effect on elastomer film strength. The amounts of unreacted PDMS and (QM OEt )8 over time were calculated from 1 H-NMR spectra ( Figure A3), and the results are summarized in Figure 7.…”
Section: Silsesquioxane Cross-linkermentioning
confidence: 99%
“…The concentration of the unreacted cross-linker decreased over time, reaching 0 wt% after 17 days as additional cross-linker domains were created. Since silsesquioxanes are generally known to be self-reinforcing cross-linkers [16][17][18][19][20][21], (QM OEt ) 8 cross-linker domains are expected to have a positive effect on elastomer film strength. The amounts of unreacted PDMS and (QM OEt )8 over time were calculated from 1 H-NMR spectra ( Figure A3), and the results are summarized in Figure 7.…”
Section: Silsesquioxane Cross-linkermentioning
confidence: 99%
“…The incorporation of SR into the nanocomposite can enhance the chain entanglements and cohesion of the ingredients, which restrict the molecular chain and reduce the distance of the molecular network. This phenomenon leads to the reduction of the surface energy and improvement of the hydrophobicity 32 . The present nanocomposite represented improved hydrophobicity in comparison with a similar antibacterial film in Reference [33].…”
Section: Resultsmentioning
confidence: 61%
“…In addition, the chemical shift at 0.42–0.63 ppm was assigned to the proton peaks of C–CH 3 , and the characteristic peak at 1.70–1.79 ppm corresponded to the proton of tertiary carbon (C–H). However, strong signals for the protons of the Si–CH 2 CH 2 CH 2 –Si groups were also observed at chemical shifts of 1.01–1.13, 1.41–1.55, and 2.19–2.25 ppm, which indicated that the hydrosilylation of HMQ and eugenol was carried out as a result of α-addition and β-addition products, dominated by β-addition [8,29]. Meanwhile, the chemical shifts of Si–H occurring at 4~5 ppm and vinyl of eugenol at 5~6 ppm were not found.…”
Section: Resultsmentioning
confidence: 99%
“…MQ silicone resin can be used as a constituent of a high-temperature coating, as a tackifier for a silicone pressure-sensitive adhesive, and as a filler for liquid silicone rubber [7]. MQ silicon resin is used as a reinforcing agent in a polymer matrix, which can significantly improve the mechanical properties and thermal stability of the composites, and further improve their application value [8].…”
Section: Introductionmentioning
confidence: 99%